2010
DOI: 10.2174/138920010792927316
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Tyrosine Kinase Inhibitors with the MDR-Related ABC Transporter Proteins

Abstract: Tyrosine kinase inhibitors (TKIs) are a new class of highly-selective and molecularly targeted anticancer agents. Most of these newly developed TKIs are hydrophobic, thus allowing them to rapidly penetrate the cell membrane to reach their specific intracellular targets. However, their therapeutic potential could be significantly hindered by the overexpression of certain ATP binding cassette (ABC) membrane transporters, which extrude hydrophobic drugs and result in cellular resistance to TKIs by tumor cells. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 128 publications
0
30
0
Order By: Relevance
“…The broad or polyspecificity of P-gp is legendary (or infamous), and the list of compounds known to interact with this transporter is well in excess of 300 (Wang et al, 2011;. It is apparent that many of the much touted "new generation" anticancer compounds (e.g., kinase inhibitors) are also substrates for transport by P-gp (Hegedus et al, 2002;Wang and Fu, 2010). There is a clear need to generate compounds, or strategies, to overcome the actions of P-gp in 1) limiting the effectiveness of chemotherapy in cancer and 2) influencing the pharmacokinetic profile of a vast number of clinically prescribed drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The broad or polyspecificity of P-gp is legendary (or infamous), and the list of compounds known to interact with this transporter is well in excess of 300 (Wang et al, 2011;. It is apparent that many of the much touted "new generation" anticancer compounds (e.g., kinase inhibitors) are also substrates for transport by P-gp (Hegedus et al, 2002;Wang and Fu, 2010). There is a clear need to generate compounds, or strategies, to overcome the actions of P-gp in 1) limiting the effectiveness of chemotherapy in cancer and 2) influencing the pharmacokinetic profile of a vast number of clinically prescribed drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, TKIs have been identified as inhibitors of several ATP-binding cassette (ABC) efflux transporters that are commonly upregulated in cancer cells including P-glycoprotein (multidrug resistance protein 1), breast cancer resistance protein (BCRP), and multidrug resistance-associated protein (MRP) 1 [10][11][12][13][14][15][16][17][18]. ABC efflux transporters consist of a large family of membrane-spanning proteins involved in the active extrusion of substrates such as endogenous molecules, drugs, and drug metabolites from the cell through hydrolysis of ATP [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of TKIs targeting different oncogenic signaling pathways have been developed, and are currently used in the clinic or being tested in clinical trials. Interestingly, it has been reported that several TKIs, such as gefitinib, imatinib, and lapatinib can interact with ABCG2, thereby inhibiting its drug transport activity and enhancing the anticancer efficacy of conventional chemotherapeutic agents (4). Importantly, various recent studies have reported favorable clinical outcome by combining TKIs with conventional cytotoxic agents or monoclonal antibody in cancer chemotherapy (5,6).…”
Section: Introductionmentioning
confidence: 99%